GENDER EQUALITY IN SHE'S THE MAN MOVIE DIRECTED BY ANDY FICKMAN: FEMINISM APPROACH - MAULANA, CHANDRA (2007)
The object of this research is the movie entitled She's The Man by Andy Fickman. The major problem of this study is how struggle for gender equality is reflected in the movie She's The Man by Andy Fickman based on feminism approach. The researcher employs a qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is the movie itself. The secondary data sources are the books about the social historical background of American society, some books about feminism and the other sources such as internet. The method of data collection is library research and the technique of data collection is descriptive technique. The result of the study reveals the relationship between the movie and the social reality in American reflects the women struggle for gender equality. Andy Fickman wants to say that men and women are created equal.